Physiological changes and the Mallampati classification: Tracheal intubation complications (International Seven Journal of Health Research, 2024)
Introduction: Difficulty in tracheal intubation is a significant factor in morbidity and mortality. Mallampati has therefore made it possible to predict it in advance. Its classification is based on the visualization of pharyngeal structures and is a simple anesthetic assessment. In practice, some circumstances can modify Mallampati's classification, making intubation more complex, and knowledge of these is of medical importance. Objectives: To review the literature on circumstances that alter Mallampati's classification. Methods: A literature review was carried out on possible physiological alterations responsible for changes in the Mallampati classification. We searched the Medline, Scielo and CRD databases for the terms: “Mallampati modification” and “Mallampati score” associated with “anaphylaxis” and “labor” and the articles were submitted to critical analysis. Results: Among the interferences in the Mallampati score is anaphylaxis, which results in upper airway edema, affecting the classification. In addition, pregnancy and labor can influence the score. Some factors such as breast growth, weight gain and pharyngeal edema increase the index in pregnant women. In addition, there is airway edema, explained by exertion and increased venous pressure in the upper body. In addition, fluid overload and the antidiuretic effect of oxytocin cause changes in the airways. Another situation is that of pediatric patients, where 13% of respiratory problems during anesthesia are related to intubation difficulties. In children between 4 and 8 years old without malformations, the index has proved applicable. However, it is impossible to use it in children under 4 years of age. Conclusions: The Mallampati score complements the judgment of a general examination that includes anamnesis and physical inspection of the craniofacial structure to identify risk factors, taking into account other situations that may interfere with the classification. Therefore, an understanding of its limitations is necessary for its correct application.